QUTPE - CUSTOMER WAIT TIME MANAGEMENT PLATFORM - Ruslan, Shaimerdenuly; Sanzhar, Abdulin; Margulan, Zholaman; Bekzat, Aitbekov; Akbolat, Nurbek (Nazarbaeyv University School of Engineering and Digital Sciences, 2024)
In a rapidly developing environment, such as a public space, the set of people's time is of vital importance. In banks, hospitals and shopping centers - a fair share of time can be spent standing in line. The Qutpe Customer Wait Time Manager is designed to revolutionize traditional queuing practices in busy public places. By digitalizing the queue management process and allowing users to virtually join a queue and monitor their place in line in real-time status, the Qutpe app effectively reduces wait times and ambiguities with queuing. Faced with uncertainty and long in many public spaces in Astana, the team was inspired to create a queuing app using modern technologies and queuing theories to eliminate uncertainty and increase the efficiency of service. This report outlines the development of the Qutpe system, detailing the project approachᅳincluding the algorithms and technologies used, like Django for backend development and PostgreSQL for database management. The document also covers project execution challenges and successes, evaluation methods, and potential future enhancements to ensure the system's adaptability and long-term usability in Kazakhstan and potentially other markets.
Kutpe app
Keywords: Type of access: Open access; queue; AI; LLM integration; web app; Queueing theory